Factors determining teleworking before and during COVID-19: some evidence from Spain and Andalusia - Caparrós-Ruiz, Antonio (Emerald, 2022)
This article analyses the inequalities in access to teleworking in Spain. Specifically, the study examines what factors determine remote working in a pre-pandemic period and during the state of alarm (March 2020). Moreover, we examine whether telecommuting is related to the likelihood of suffering emotional disorders during lockdowns. The methodological approach followed to analyse access to teleworking mainly consists of the estimation of ordered response models. Two datasets are used: the first is the Survey on Equipment and Use of ICTs in Households, conducted by the Spanish National Statistics Institute (INE) in the pre-pandemic period (2018). The second is the Social Survey 2020. Habits and Living Conditions of the Andalusian Population during the State of Alarm, conducted by the Institute of Statistics and Cartography of Andalusia (IECA) once the state of alarm was declared. The results indicate that ICT training is a key element in helping to explain the likelihood of working from home. However, some groups of workers might experience difficulties in their transition to teleworking. This could increase labour market segmentation and hinder the transition to the knowledge economy. Moreover, the findings detect that employees working both on the company premises and from home are more likely to suffer emotional disorders. The article sheds new empirical evidence on teleworking in Spain and Andalusia, including some novel methodological aspects to estimate the regressors’ effects on the probability of working from home.
This research corresponds to the article titled “Factors determining teleworking before and during COVID-19: some evidence from Spain and Andalusia” published by the review Applied Economic Analysis (Vol. 30 No. 90, pp. 196-212).
Keywords: Teletrabajo; Teleworking; ICTs; COVID-19; State of Alarm